1990
DOI: 10.1016/0735-1097(90)90590-l
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the automatic implantable cardioverter-defibrillator in prolonging survival in patients with severe underlying cardiac disease

Abstract: The ability of the automatic implantable cardioverter-defibrillator to prolong overall survival, particularly in patients with significantly depressed cardiac function, has not been well documented. Of 119 patients who received the implantable defibrillator in this institution, 40 had a left ventricular ejection fraction less than 30% (Group A) and 79 had an ejection fraction greater than or equal to 30% (Group B). For each group, cumulative survival was compared with the projected survival if the implantable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…319,322,323 Multiple analyses have supported the notion that patients with reduced LV function may experience greater benefit with ICD therapy than with drug therapy. 320,[335][336][337][338] All patients undergoing evaluation for ICD therapy should be given optimum medical treatment for their underlying cardiovascular condition. 16 Patients experiencing cardiac arrest due to VF that occurs more than 48 hours after an MI may be at risk for recurrent cardiac arrest.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…319,322,323 Multiple analyses have supported the notion that patients with reduced LV function may experience greater benefit with ICD therapy than with drug therapy. 320,[335][336][337][338] All patients undergoing evaluation for ICD therapy should be given optimum medical treatment for their underlying cardiovascular condition. 16 Patients experiencing cardiac arrest due to VF that occurs more than 48 hours after an MI may be at risk for recurrent cardiac arrest.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…The ICD was originally designed to prevent SCD in patients with life-threatening, sustained ventricular arrhythmias [223][224][225][226] . It was soon demonstrated that ICDs were effective in the reversion of sustained ventricular tachycardia and fibrillation [227][228][229][230] .…”
Section: Implantable Cardioverter Defibrillatormentioning
confidence: 99%
“…2,3 Small retrospective studies have used the incidence of "appropriate" therapies delivered by the devices to estimate the potential benefit from ICD implantation. 2,4 As a more rigorous variant of this approach, we previously suggested use of the recurrence of fast (Ͼ240 bpm) ventricular tachyarrhythmias documented by the memory of the device to calculate hypothetical mortality curves. 5 This was based on the assumption that the tachyarrhythmia would have been lethal had it not been terminated by the device.…”
Section: T He Implantable Defibrillator (Icd) Introduced By Mirowski mentioning
confidence: 99%